Addressing power imbalance in research: exploring power in integrated knowledge translation health research - Jacqui Cameron; Anita Kothari; Renee Fiolet (Research Involvement and Engagement)
Abstract Introduction Integrated knowledge translation (IKT) is a knowledge translation framework that focuses collaboration between researchers and knowledge users (KUs) to generate research findings. KUs can be policymakers, clinicians, or those with lived experience who partner with researchers. While advocated as an approach that democratizes research and reduces power imbalance between researchers and KUs, it is not known if the implementation of IKT by health researchers actively addresses power imbalances. The aim of this study was to review research using an integrated knowledge translation approach to explore how power is addressed within these research studies. By looking broadly at how the studies addressed/described/discussed/dismantled power we explored examples of when this was done well and not so well, exposing the assumptions sometimes made by researchers. Methods We drew from systematic review procedures combined with a modified critical discourse analysis (CDA) lens. We searched Medline, PsycINFO, CINAHL, Scopus, Social Science Database, SocIndex and Google Scholar for English language studies that focused on IKT and power. Data were extracted on study characteristics and a modified CDA which included questions in relation to power (e.g., description of power, phrases used to describe power, evidence of power dynamics, strategies for addressing power imbalances) and end user engagement (e.g., Did they ask KUs how they wanted to be involved? Did they engage in reflection with KUs? Did they discuss dissemination strategies with KUs). Results Eleven studies were eligible after screening 381 titles and reviewing 40 full-text studies. The use of IKT to address power varied significantly, revealing both positive examples as well as some missed opportunities to address power imbalances from study inception to dissemination. Conclusion Revisiting the use of IKT to examine how power is defined, shared, and managed in relationships with KUs could provide valuable insights. Using a CDA framework to explore these dynamics would indeed address the nuances of power in research contexts. Future research should focus on developing strategies to effectively implement IKT to address power imbalances, leading to research that has a better chance of being useful, usable and used in practice.